Stable isotopes unravel the feeding mode–trophic position relationship in trematode parasites. Issue 2 (15th December 2021) - Sabadel, Amandine J. M.; MacLeod, Colin D.
Abstract: Stable isotopes have been sporadically used over the last two decades to characterise host–parasite trophic relationships. The main reason for this scarcity is the lack of an obvious pattern in the ratio of nitrogen stable isotope values ( δ 15 N) of parasites in comparison to their host tissues, which would be key to understand any host–parasite system dynamics. To circumvent this, we focused on a single snail host, Zeacumantus subcarinatus, and three of its trematode parasites. We used stable isotopes to investigate each host‐trematode trophic relationship and shed light on the mechanisms utilised by the parasite to reroute its hosts' biomass. All our trematodes were found to be 15 N‐enriched compared to their host, with their δ 15 N values strongly related to their feeding behaviours: passive versus active. It was possible to 'rank' these parasite species and assess their 'relative' trophic position using δ 15 N values. We also demonstrated that including a broader range of samples (e.g. host food and faeces, multiple parasite life stages) helped understand the metabolic mechanisms used by the various participants, and that using carbon stable isotope values and C:N ratios allowed to identify an important lipid requirement of these trematode parasites. Finally, we show how critical it is to not ignore parasitic infections as they can have a great influence on their host's trophic position. We have shown that by focussing on a single host species and a single taxonomic group of parasites, we can remove a certain amount of variation recorded by broader isotope studies. We hope that these data will ultimately improve our ability to place parasites in food webs, and thus improve our understanding of the connections and interactions that dictate food web dynamics. Abstract : This research demonstrates how stable isotopes can help shed light on the intimate trophic relationship between a parasite and its host. Authors investigated and compared how three trematode parasites with distinct feeding modes (active vs. passive) rerouted the biomass of their host, a marine snail, in different ways.